The Management of Opera (1861-1918) Theatres of the Eastern Adriatic - Scuderi, Cristina (2023)
This study offers a glance into the dense network of relationships between impresarios, theatre managers, singers, musicians and publishers who populated the multicultural territory of the Eastern Adriatic theatres in the period between 1861 and 1918. A detailed reconstruction provides insight into how opera performances were organised, from the initial search for funding, through the choice of repertoires, up to the closing of contracts with artists.